Simulation of a new pipe design for erosion reduction in curves - Duarte, Carlos Antonio Ribeiro (2017)
Pneumatically conveyed particles are commonly responsible for triggering the erosion process by impacts on the wall. Those impacts result from the fluid-particle interaction and understanding its mechanisms is the key to mitigate the erosion damage in engineering applications. In general, erosion due to particle impingement, which can occur in a variety of practical cases, is often the key factor in pipeline failure. Parts such as elbows, for instance, are particularly prone to erosion issues. In the first part of this thesis, the Unsteady Reynolds Averaged Navier-Stokes (URANS) equations are combined with a stochastic Lagrangian particle tracking scheme considering all relevant elementary processes (drag and lift forces, particle rotation, inter-particle collisions, particle-wall interactions, coupling between phases) to numerically predict the erosion phenomenon on a 90 elbow pipe. After a detailed validation of the erosion model based on the experimental data of Solnordal et al. (2015), several cases regarding the wall roughness and static and dynamic coefficients of friction are analysed to elucidate the nature of the erosive process. For such analysis, more fundamental variables related to particle-wall interactions (impact velocity, impact angle, impact frequency) were used to scrutinize the basic erosion mechanisms. Finally, to prove the importance of inter-particle collision on elbow erosion, different mass loadings are additionally simulated. Especially for the high mass loading cases, interesting results about the role of the inter-particle collisions on elbow erosion are enlightened. In a second step, we propose a novel pipe wall design in order to reduce the erosion on a 90 elbow. This design consists of twisting the pipe wall along the flow streamwise direction. Basically, such configuration generates a swirling motion of the flow upstream of the elbow and consequently re-disperse the transported particles, preventing them to focus on a single point at the elbow. Based on a four-way coupled simulation, the simulations were run for the new pipe wall design. To understand the nature of the erosive process on the new pipe wall design, the above-mentioned variables regarding the particle-wall interaction were evaluated. In general, it was found that the changes in the multiphase flow promoted by the twisted pipe wall are effective for reducing elbow erosion. The numerical simulations reveal that the pipeline equipped with a twisted pipe wall reduces the peak of erosion depth up to 33% on the elbow when compared to the conventional pipe.